Ensino do voleibol nas aulas de Educação Física nas escolas da cidade de Arraias-Tocantins - Conceição, Juvani Ferreira da (Universidade Federal do Tocantins, 2024)
One of the contents of physical education is team sports, including volleyball, the object of the current research. The literature shows that this content is one of the most applied in the school context. In this sense, this study problematizes the way in which teachers with training in physical education adopt volleyball content in Physical Education classes in schools in the city of Arraias,Tocantins, Brazil. This research is focused on the ways in which teachers relate to the aforementioned teaching content and what methods are used to share knowledge about sport during their classes, the challenges and difficulties they face. For this, case study research was used a semi-structured questionnaire. Which covered: teaching training and experience, the approaches and contente worked, assessment practices and assessed contente and the difficulties faced in sharing volleyball contente with students. The data collected shows that teachers have a lot of experience in the classroom, however, they need to give greater organicity to their work from the point of view of sharing volleyball. We also see a movement of disinvestment in their career, as they do not continued their training at postgraduate level.